The Effect of Construction Process Sustainability, Material Efficiency, and Time Management on Commercial Building Project Productivity in Tangerang - Sono, Mohammad Gifari; Suda Nurjani , Ni Putu; Alfred D.D, Petrus Jhon (Westscience Press, 2024)
This study examines the influence of construction process sustainability, material efficiency, and time management on the productivity of commercial building projects in Tangerang. Employing a quantitative approach, data were collected from 150 respondents, including project managers, site engineers, and supervisors, through a structured questionnaire using a Likert scale of 1-5. Data analysis was conducted using SPSS version 25. The findings reveal that all three factors significantly and positively affect productivity, with time management emerging as the strongest predictor. These results highlight the importance of integrating sustainable practices, efficient resource utilization, and effective scheduling to enhance project outcomes. This study provides actionable insights for stakeholders in the construction industry, contributing to the broader discourse on sustainable and efficient construction practices.